Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions



we know that  log(m) + log(n) =log(mn) . so that  => log(1)+log(2)+log(3)=log(1x2x3)


and   log(1+2+3)=log(3+3)=log(6)

    there fore  =>  log(1+2+3)=log1+log2+log3

                       =>  log6=log6

                            hence proved 

1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts